การบังคับใช้คำสั่งของสหภาพยุโรปว่าด้วยว่าด้วยการตรวจสอบสถานะความยั่งยืนขององค์กรนอกอาณาเขต: ศึกษากรณีสิทธิแรงงานเมียนมาร์ - เน โม โม อุ้ (จุฬาลงกรณ์มหาวิทยาลัย, 2023)
The aftermath of Myanmar’s Spring Revolution has devastated the country’s socio-economic endeavours impacting the lives of all citizens. This thesis particularly highlights the lives of Myanmar workers in the garment sector who are being exploited due to the lack of effective Labour Rights protection by the Government and explores alternative ways to protect the workers. The European Union’s Directive on Corporate Sustainability Due Diligence (the EU Directive) has recently been approved by the European Council. It is currently on the verge of being interpreted by its member countries. This Directive mandates and legalizes the Human Rights Due Diligence (HRDD) for multinational corporations. Particularly, the Directive requires them to oversee the HR protection practices throughout the entire value chain and takes them accountable if adverse human rights impact is caused in such value chain. This thesis assesses whether this Directive could serve as an alternative for protecting the rights of Myanmar’s workers. The analysis posits that, in theory, the Directive s extensive scope could encompass Myanmar, and thus, the mandatory HRDD requirements of the EU Directive could potentially offer effective Labour Right protection for Myanmar’s workers.